Urban Poverty and Suffering in Nepal - Acharya, Bala Ram (International Research Journal of MMC, 2026)
Urban poverty mainly in the under developing regions is a condition in which people live with a lack of adequate income, basic housing and access to opportunities and social inclusion. This study aims to examine the nature of urban poverty and the different nature of suffering among squatter households in Thapathali squatter settlement situated in Kathmandu Metropolitan City, in a multidimensional way. This study explores comprehensive forms of poverty beyond income-based measures only. It analyzes how economic insecurity is associated with education, health access, housing conditions, and psychological stress. The study applied comparative research design basically within a quantitative approach. It used a household survey under a simple random sampling method. The survey for this research was conducted in March–April 2023 and data were collected using a structured household questionnaire. The analysis was conducted using descriptive statistics, including frequency, percentage, and cross-tabulation to examine the reflection of urban poverty in the squatter settlement. It was used to examine patterns and relationships of poverty across key dimensions of deprivation to explore multidimensional nature poverty from the ground level. The findings show that most households depend on informal and insecure employment due to the status of less capability. A large proportion of households in urban squatter settlement experienced from low income and exclusion of education, health and housing security. These deprivations are closely associated with the insecure psychology of the respondents known as social nature of poverty. The situation promotes stress and feelings of social humiliation among them due to exclusion. The study concludes that urban poverty among squatter communities in Kathmandu is structurally produced through long-term unaccountable political processes and state-based exclusion.